Processo como experimentalismo na educação estética e artística - Consiglieri, Joana (2018)
The main goal of this article is to understand and practice the process as experimentalism, in Aesthetic and Art Education, in particular Visual Arts, in Portugal, mainly, in nursery and primary schools. It is a study about the recent learning and artistic practice in teacher training college, in which the process is more important than the product of the art production. The aesthetic experimentalism allows the converging of the creative process and creativity with artistic knowledge of the National Curriculum and Classroom